A Novel, Nonaquatic Zoonotic Transmission of Mycobacterium marinum - Georgios Kravvas; Nada Aboukhatwah; Lola Meghoma; Victoria Vilenchik; Jon Oxley; Daniel Keith (Case Reports in Infectious Diseases)
Conclusion: Mycobacterium marinum infection should be considered in patients with indicative clinical and histological features, especially in the immunocompromised, even in the absence of an obvious aquatic source of infection. Awareness of this entity could lead to earlier diagnoses and reduced morbidity and mortality.